PEMBINAAN NARAPIDANA ANAK DI LEMBAGA PEMASYARAKATAN ANAK SEI. BULU MUARA BULIAN - Hafrida, Hafrida; Monita, Yulia; Siregar, Elisabeth (Prodi PGSD FIP UNM, 2015)
This research is a multi-years research that is planned to be completed in 2 (two) years. In this year this research aims to see the implementation of child offender in The Children Penitentiary Sei. Bulu Muara Bulian Jambi. This research is an ?Empirical Research?, that conducted field research on The Child Penitentiary Sei. Bulu Muara Bulian, and conduct interviews to Children Inmates and observations tothe implementation of the development ofthe children inmates, in addition this research also conducted on The Law and Human Rights Ministry of Jambi. The result of the research shows in The Children Penitentiary Sei. Bulu Muara Bulian Jambi not only populated by children in mates, but also combined with adult female in mates. The result of the field research on the 27 may 2015 the number ofadult female in mates reached47 (Forty-seven) people, the number ofchildinmatesare36 (thirty six) people. The results offield research hasserious problems: 1) from Goal of Development aspect ofthere isa big differences, the purpose of fosteringa child in mates are education and training while the fostering goal of adult women in mates are correctional. 2) From the practical aspectsof the available labor builder is a builder who should have the power (tupoksi) to foster in mates child obtains heavier burden than duties that are supposed, the obligation to implement the guidance to adult female in mates. 3) From the aspect of facilities there is no additional facilities relating with the increasing of the work load. 4) from the aspects of employee resources builder also there is no special addition.The head of the law Ministry and Human Rights Jambi province says the consideration of the merger because of the proximity characteristic still possible to combine. Seeing the empirical condition shows the needs for the application of Law No.11 of 2012 concerning Juvenile Justice System where the children criminals tries to avoid a child in the punishment imprison ment through the efforts diversion andrestorative justice. The research on the effectiveness of restorative justice through the application of this diversion will be continued in the research studyon the second year. Keywords: Inmates Children, Children Penitentiary, Development of Inmates Children.